On the full coupling of plastic anisotropy and anisotropic ductile damage under finite strains. (September 2017) - Badreddine, Houssem; Saanouni, Khemais
In this work, thermodynamically consistent, non-associative and fully anisotropic elastoplastic constitutive equations strongly coupled with ductile anisotropic damage developed in previous work are used to study the responses of the proposed model under various simple and complex loading paths. First, the complete set of the fully coupled non-associative constitutive equations based on the rotated frame formulation (RFF) for finite strains is summarized and shortly discussed. Then, the effect of the rotating frame in the model response is analyzed on the light of typical loading paths. The influence of the induced plastic anisotropies on the evolution of the anisotropic ductile damage is investigated. Finally, the responses of the model for non-proportional loading paths are studied, compared and discussed with respect to the initial and induced anisotropies of the plastic flow and the ductile damage evolution as well as with respect to the rotating frame choice.